Déficit de aprendizagem na visão da inclusão : material alternativo como facilitador da aprendizagem de operações de cálculos numéricos : estudo de caso - Arruda, Zeina Aparecida de (2017)
Although difficulties or learning disorders appear to be well defined in the school context and have become the focus of research in recent years, they are still poorly understood by society at large. We still have difficulties in defining the paths that lead to learning. This is acceptable since the term 'learning difficulties' does not refer to a single disorder, but a variety of problems that delay the student's cognitive and academic development. In order to aid in the understanding of Learning Difficulties (AD), the study presented in this paper aimed to unveil, investigate and analyze the elements that hamper the capacity of the logical reasoning required in the operations of numerical calculations, of a student with Multiple physical disabilities and learning deficits, since it is inconceivable to admit that a child in the stage of discovery and development has not progressed from one year to the next. This aspect makes us question the current system of excluding education, which gives us the idea that education is for everyone. To achieve this goal, a qualitative research was carried out, in the case study modality, together with a public elementary school in the city of Denise, State of Mato Grosso; Guiding us through David Ausubel's Significant Learning Theory (TAS). After this investigation with the construction and implementation of a didactic tool - Instructional Guide - it was intended to attest to its effectiveness as a facilitator in the teaching teaching process of numerical calculations of students with dyscalculia.